SCREENING THE ANTI BIOFILM ACTIVITY OF BIOSURFACTANT AND ITS APPLICATION AS AN ALTERNATIVE BIOCIDE IN CONTROLLING BIOCORROSION - ZAHRA PUTRI (NIM : 21116034), FADILLA
Biocide is a compound that can be used to eliminate the microorganisms caused biocorrosion. It is estimated about 40% of the corrosion occurring in the industry is caused by biocorrosion. This problem cause the use of biocide unavoidable. Biocides that commonly used are derived from synthetic compounds that are toxic and harmful for the environment so finding an alternative biocide that not toxic and environment-friendly is required. Biosurfactant which is produced by bacteria is an amphiphilic substance that not only used for enhanced oil recovery but potentially used as an alternative biocide because some biosurfactant has the antibiofilm activity. Biosurfactants that not only enhanced oil recovery but also act as biocides are more valuable, especially in the oil and gas industry. Therefore, the research of screening of biosurfactants that has antibiofilm activity was done to biofilm on carbon steel St-37 coupon. The biosurfactant screening was conducted using broth microdilution method in microtiter kepinge 96 wells for comparing the level of biofilm eradication, the values of MIC (Minimum Inhibitory Concentration), MBIC (Biofilm Minimum Inhibitory Concentration), and MBEC (Minimum Biofilm Eradication Concentration) of biosurfactant against biofilm-forming consortium bacteria. The results of the screening showed that biosurfactant from the isolate of G3 that can enhanced oil recovery has the best eradication level about 68.3% at a concentration of 100 μg/mL with MIC, MBIC50, MBIC90 and MBEC50 values were 50, 25, 25, and 25 μg/mL. Besides that, the MBEC value of biosurfactant of G3 isolate for biofilm on carbon steel coupon at hydrostatic state and effect of biosurfactant of G3 at biofilm on carbon steel coupon at hydrodynamic state were also conducted. MBEC value of biosurfactant from G3 isolate against biofilm on the carbon steel St-37 coupon at hydrostatic state can be obtained at a concentration of 75 μg/mL and the highest decreasing of corrosion rate (59,8%) was obtained at a concentration of 200 μg/mL for 6 hours. Biosurfactant of G3 isolate with a concentration of 200 μg/mL against biofilm on carbon steel St-37 coupon with a hydrodynamic state can also eradicate the biofilm more than 50% and reduce the rate of corrosion of metals by 34.1%. Based on these results, biosurfactant produced by G3 isolate is potential to be an alternative biocide for controlling biocorrosion.